Efficacy of Linezolid in the management of pneumonic COVID-19 patients. Bioinformatics-based clinical study - Eid, Ragaey A; Elgendy, Marwa O; Sayed, Ahmed M; Abdallah, Abdelrahman M; Mostafa, Hayam MA; Mohammed M Elsisi, Ahmed; Hamed, Ahmed M; Shaker, Marwa Abdallah (The Journal of Infection in Developing Countries, 2024)
Introduction: At the beginning in July 2023, there has been a significant increase in daily hospital admissions attributed to the new variant of COVID-19. Aim of this study is to explore the clinical benefits and outcomes of using linezolid in the management of pneumonic COVID-19 patients. Methodology: The study included 230 patients with SARS-CoV-2 infection confirmed by RT-PCR. Group 1: 118 patients were managed with Linazolid alongside steroids. Group 2: (control group) patients treated according to the Protocol for Egyptian COVID-19 management outlines and WHO guidelines (112 patients). Each patient group was categorized into 3 age groups: 20-40 years, 41-65 years, and over 65 years. Patients were carefully followed up until recovery or mortality. A docking analysis was carried out to investigate the potential of linezolid to act as an Mpro inhibitor. Results: Group 1's average recovery time was 15.1 days in contrast to 18.7 days for Group 2 (control). There were no deaths reported. In silico investigations revealed that Linezolid was able to achieve a binding mode comparable to that of the co-crystalized inhibitor. Conclusions: Linazolid is considered an effective antiviral weapon against SARS-COV-2. It could be used in the management plan of pneumonic individuals due to SARS-COV-2 infection. We recommend using it to combat the current wave caused by Omicron EG-5 Variant.